The Subjective Need for Social Interaction - Bertolín-Guillén, Jose Manuel (British Journal of Healthcare and Medical Research, 2023)
Introduction: With regard to emotional phenomena, the aim of this thematic review is to provide a synthesis of the most recent and highest-quality psychological and psychobiopathological information, endorsed by the scientific community. Material and Method: A relevant electronic and manual search of several major national and international repositories, directories and bibliographic databases has been carried out until the end of March 2023. Results and Discussion: Well-known strategies of predictive regulation or allostasis are discussed in relation to human emotions, feelings and interactions. Emotions will be able to induce feelings, which will influence personal actions mutually. Psychobiologically, the default or default-operating neural network is important in any interactions. Distinct networks of the so-called social brain display volumetric changes in the presence or absence of social support groups. Social connection and interaction are a strong preventive factor for psychopathologies such as anxiety, depressive and personality disorders. On the other hand, interoceptive awareness, linked to empathy, is key to social interaction. Understanding of personal interrelationships is shaped in the brain regions that are considered social cognitive. Dysfunctional social behaviours may be strongly conditioned by genetic as well as environmental factors. Furthermore, one should consider both individual cognitive reserve and cognitive performance. Conclusions: The known relationships between emotions, feelings and personality with respect to human interactions have been made succinctly explicit. Also, where relevant, the psychobiopathological influence on personal relationships and communication skills.